Nursing actions in home palliative care for the elderly supported by multidimensional assessments: integrative review (Research, Society and Development, 2021)
Objective: To analyze the nursing actions that are systematized by the use of multidimensional assessment instruments during palliative care assistance to the elderly at home. Method: Integrative review of articles published between 2011 and 2020, identified in the MEDLINE, LILACS, BVS, BDENF and IBECS, CINAHL databases, in Portuguese, English or Spanish; with abstracts and/or text available for full reading and free access, seeking to answer the research question “In the PC for elderly people, the nurse's assessment using assessment instruments adopted in other care contexts guide nursing actions in palliative home care?”. Results: From the searches in the databases, 242 articles were identified, of which 19 were included in the present study, enabling the identification of multidimensional assessment instruments and focuses of nursing action. Conclusion: The scope and complexity of nurses' activities in the context of home palliative care was evidenced, involving the management of care needs and the promotion of targeted actions, with a multidimensional and holistic character.